Personalized Epigenome Remodeling Under Biochemical and Psychological Changes During Long-Term Isolation Environment - Liang, Fengji; Lv, Ke; Wang, Yue; Yuan, Yanhong; Lu, Liang; Feng, Qiang; Jing, Xiaolu; Wang, Honghui; Liu, Changning; Rayner, Simon; Ling, Shukuan; Chen, Hailong; et al. (Frontiers in Physiology, 2019)
It has been reported that several aspects of human health would been disturbed during the long-term isolation environment (for instance, Mars-500 mission), including psychiatric disorder, circadian disruption, temporal dynamics of gut microbiota, immune response, and physical-activity-related neuromuscular performance. Nevertheless, the mechanisms underlying these disturbances and the interactions among different aspects of human adaption to extreme environmental remain to be elucidated. Epigenetic feature, like DNA methylation, might be a linking mechanism which explains the involvement of environmental factors linking human genome and health outcome. We conducted personalized longitudinal DNA methylation patterns of peripheral whole blood cells profiling of six subjects across 6 sampling points in Mars-500 mission. Specially, we developed a Personalized Epigenetic-Phenotype Synchronization Analysis (PeSa) algorithm to explore glucose- and mood-state-synchronized DNA methylation sites, focusing on finding the dynamic associations between epigenetic patterns and phenotypes in each individual, and exploring the underling epigenetic connections between glucose and mood-state disturbance. Results showed that DMPs (differentially-methylated-probes) were significantly enriched in pathways related to glucose metabolism (Type II diabetes mellitus pathway), mood state (Long-term depression) and circadian rhythm (Circadian entrainment pathway) during the mission. Furthermore, our data revealed individualized glucose-synchronized and mood-state-synchronized DNA methylation sites, and PTPRN2 were found associated with both glucose and mood state disturbances across all six subjects. Our findings suggest that personalized phenotype-synchronized epigenetic features could reflect the effects on human body, including the disturbances of glucose and mood states. The association analysis of DNA methylation and phenotype, like PeSa analysis, could provide a new possibility for understanding the intrinsic relationship between phenotypic changes of human body adapting to long-term isolation environmental factors.